QUBIC IV: Performance of TES bolometers and readout electronics. Issue 4 (1st April 2022) - ; Piat, M.; Stankowiak, G.; Battistelli, E.S.; de Bernardis, P.; D'Alessandro, G.; De Petris, M.; Grandsire, L.; Hamilton, J.-Ch.; Hoang, T.D.; Marnieros, S.; Masi, S.; et al.
Abstract: A prototype version of the Q & U bolometric interferometer for cosmology (QUBIC) underwent a campaign of testing in the laboratory at Astroparticle Physics and Cosmology laboratory in Paris (APC). The detection chain is currently made of 256 NbSi transition edge sensors (TES) cooled to 320 mK. The readout system is a 128:1 time domain multiplexing scheme based on 128 SQUIDs cooled at 1 K that are controlled and amplified by a SiGe application specific integrated circuit at 40 K. We report the performance of this readout chain and the characterization of the TES. The readout system has been functionally tested and characterized in the lab and in QUBIC. The low noise amplifier demonstrated a white noise level of 0.3 nV/√Hz. Characterizations of the QUBIC detectors and readout electronics includes the measurement of I-V curves, time constant and the noise equivalent power. The QUBIC TES bolometer array has approximately 80% detectors within operational parameters. It demonstrated a thermal decoupling compatible with a phonon noise of about 5 × 10 -17 W/√Hz at 410 mK critical temperature. While still limited by microphonics from the pulse tubes and noise aliasing from readout system, the instrument noise equivalent power is about 2 × 10 -16 W/√Hz, enough for the demonstration of bolometric interferometry.